The Functionalisation of Terpenes Towards Amphiphilic Materials - Fowler, Harriet (2024)
The aim of this thesis was to develop robust functionalisation strategies of various terpenes to introduce hydrophilic and hydrophobic moieties with the goal of producing amphiphilic materials that could be used in common beauty and personal care products. In the first experimental chapter, it was demonstrated that terpenoids could be utilised as functionalised initiators for the ring opening polymerisation of cyclic esters, with the aim to build surfactant-like materials. The goal of incorporating an ester functionality was to impart biodegradability into the molecule. A series of terpene-polylactide materials were synthesised, varying the initiator identity, solvent, and catalyst. It was found that these materials self-assembled in water to produce well-defined nanoparticles and had measured CAC values similar to commercial surfactant examples, thus showing a promising approach to producing renewable surfactants. In the second experimental chapter, high throughput techniques were employed with the aim of expanding the polyester library and increasing the scale of the synthesis. The use of a Chemspeed robot demonstrated the robustness of the polymerisation pathway and resonant acoustic mixing was explored as an alternative mixing strategy which demonstrated the ability to significantly reduce the amount of solvent required. The materials underwent applications performance testing at Unilever to investigate various material properties, such as cleansing, formulation, foaming and biodegradability. Unfortunately, it was concluded that the materials were not suitable for water-based formulations and did not produce stable W/O emulsions in coconut oil. From the calculated HLB values, these materials may find a use as solubilising agents or detergents. The aim of the subsequent chapters was to further exploit the interesting properties of terpenes and build hydrophobic molecules. The Alder-ene reaction was explored to produce anhydride systems with the goal of later building amphiphiles. It was shown that when alcohol functionalities were present, the reaction proceeded unexpectedly. Furthermore, the ring opening of the anhydride functionality was not simple. Terpene methacrylate monomers were synthesised and polymerised using catalytic chain transfer polymerisation with the goal of producing oligomeric materials that showed a faster biodegradation rate. The microbial biodegradation study was successful in identifying a strain of Streptomyces bacteria that could have the potential to degrade poly(methacrylate)s. Overall, the aim of the work in this thesis was to demonstrate how common terpenes and terpenoids can be used as a versatile renewable feedstock to build surfactant-like materials via different chemical transformations.